Asymptomatic testing people for SARS-CoV-2 in healthcare facilities: A systematic review - Olabisi A. Oduwole; Glory Bassey; Grace Esebanmen; Samuel Shoyinka; Johnsolomon Ohenhen; Elise Cogo; Nicholas Henschke; Eleanor Ochodo; Martin M. Meremikwu (Journal of Public Health in Africa)
Background: Asymptomatic testing involves the process whereby individuals who do not show symptoms of COVID-19 are tested for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection using any of the available laboratory test techniques.